A Study of Factors Affecting to Taxpayers’ Satisfaction of E-Filing System in Thailand - Poolsuk, Wareerat; Methavasaraphak, Preecha (Ganesha Journal, 2019)
The purpose of this research study were to study taxpayers’ satisfaction with the tax e-Filing system, and to study the factors affecting taxpayers’ satisfaction. The sample used in this research, obtained from convenient random sampling from those who submitted tax information online via e-filing of the Revenue Department in 2018, numbering 400 people by collecting data online. The results showed that the perception of convenience, perceived benefits, quality of information, and the quality of the system affected the taxpayers' satisfaction through e-payment system. The finding also indicated that the Revenue Department should develop and redesign the existing e-filing system architecture and permission of return in place to ensure convenience and ease of use to the taxpayers to motivate them to use it in the future.